Hubungan Pemberian Asi Eksklusif Dengan Pertumbuhan dan Perkembangan Pada Bayi Usia 7-12 Bulan di Puskesmas BP Nauli Kec. Siantar Marihat, Kota Pematang Siantar Tahun 2023 - Sariyani Purba; Asnita Sinaga; Indra Agussamad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Breast milk is the perfect and best food for babies, especially babies 0-6 months because it contains the nutritional elements needed for optimal growth and development of babies (Ministry of Health, 2021). Exclusive breastfeeding is breastfeeding for 6 months without giving any drinks or food, including clear water, vitamins and medicine (Ministry of Health of the Republic of Indonesia, 2020). Exclusive breastfeeding can be given directly or indirectly. Direct breastfeeding is by breastfeeding, while indirect breastfeeding is done by expressing or pumping breast milk, storing it, and then giving it to the baby. Giving breast milk based on the definition above, the mother is said to give exclusive breast milk if the baby is only given breast milk for the age of 0-6 months, while the mother is said to give non-exclusive breast milk if the baby is given other additional food or drink at the age of 0-6 months (Proverawati, 2015). Exclusive breastfeeding with growth in babies aged 7-12 months at the BP Nauli Community Health Center, Kec. Siantar Marihat Pematangsiantar City In 2023, the majority will be given exclusive breast milk with 18 people growing fat, 15 people will not be given exclusive breast milk with a normal body.The results of the Chi-square test show that with a p-value of 0.000 < 0.05, it can be concluded that there is a relationship between exclusive breastfeeding and growth in babies aged 7-12 months at the BP Nauli District Health Center. Siantar Marihat, Pematangsiantar City in 2023. Based on the results of the research, it can be seen that out of the 62 respondents, 35 babies were given exclusive breast milk (56.6%) and 27 people were not exclusively breastfed (43.5%). There were 27 mothers who did not give exclusive breast milk to their babies (43.5%). This is due to the mother's lack of knowledge about the benefits of exclusive breastfeeding and there are also mothers who work so they say they do not give exclusive breast milk to their babies because of the mother's lack of knowledge about expressed breast milk.